2018
DOI: 10.1021/acs.jpcc.8b01959
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity at the Nanoscale: Confined Liquid Dynamics and Thermal Effects in Self-Recovering Nanobumpers

Abstract: Understanding the effect of liquid viscosity in nanoconfinement is of paramount importance from both the fundamental and practical points of view. In particular, unexpected dynamic phenomena are ubiquitous in a broad range of nanofluidic applications. In this work, we used state-of-the-art high-pressure (P,V,T) calorimetry for direct observation of pressure, volume, temperature, and thermal effects during controlled intrusion/extrusion of liquids in nanoporous materials. It was discovered that the liquid extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 94 publications
(166 reference statements)
0
15
0
Order By: Relevance
“…19,45 It was also demonstrated experimentally that increasing viscosity can turn the intrusion process from endothermic to exothermic. 44 For microporous materials endothermic intrusion and exothermic extrusion was reported for MFI zeolites, 21−23 while opposite signs of thermal effects were recorded for chabazite zeolite. 46 This difference was attributed to topology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19,45 It was also demonstrated experimentally that increasing viscosity can turn the intrusion process from endothermic to exothermic. 44 For microporous materials endothermic intrusion and exothermic extrusion was reported for MFI zeolites, 21−23 while opposite signs of thermal effects were recorded for chabazite zeolite. 46 This difference was attributed to topology.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, even though the majority of the studied systems feature endothermic intrusion and exothermic extrusion, it is not the general case. When a pore is large enough for a macroscopic description to be appropriate, thermodynamics suggest that intrusion/extrusion can be endothermic or exothermic depending on the contact angle and surface entropy. , It was also demonstrated experimentally that increasing viscosity can turn the intrusion process from endothermic to exothermic . For microporous materials endothermic intrusion and exothermic extrusion was reported for MFI zeolites, while opposite signs of thermal effects were recorded for chabazite zeolite .…”
Section: Resultsmentioning
confidence: 99%
“…This is why in the literature it is often reported that wetting of cavities is irreversible [32]. One should remark that the extrusion barrier decreases with the characteristic length of the cavity; thus for nanometric lyophobic cavities (contact angle θ Y > 90 • ) extrusion can take place at positive pressures [33][34][35][36][37][38].…”
Section: (A) (B) (C)mentioning
confidence: 99%
“…Typical examples of shock-absorber HLSs include mesoporous grafted silica gels + water/aqueous solutions and recently extensions were made to metal–organic framework (MOF) + water/aqueous solution systems . MOFs, due to their unique mechanical properties, , allow additional tuning of the intrusion–extrusion process and novel applications. , Alternatives to water/aqueous systems have also been studied using ionic liquid, ferromagnetic fluids or glycerin, and glycerol. , These systems demonstrated good reproducibility and durability , and were rather quickly used as a basis to construct novel shock-absorbers and bumpers. ,, On the other hand, examples for molecular spring behavior have only been reported for the intrusion of water/aqueous solutions into a handful of microporous materials such as zeolites and MOFs …”
Section: Introductionmentioning
confidence: 99%